THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF TEACHING THE PROVERB GENRE IN PRIMARY GRADES (World Bulletin of Education and Learning, 2026)
This article provides methodological and theoretical recommendations on the specific features of teaching the proverb genre in primary grades, the importance of linguistic units in expressing one’s thoughts, and the development of pupils’ speech skills. It also presents methods for organizing lessons based on interactive approaches, examples of creative tasks, and guidelines for conducting classroom activities.
Keywords: Proverb, speech culture, creative thinking, education system, language culture, speech development, communicativeness.